STRATEGIC MODEL FOR MSME DEVELOPMENT IN MALUKU PROVINCE - Pattiruhu, Josef. R.; Tabelessy, Walter; Seleky, Roy (Journal Of Social Science (JoSS), 2023)
Micro, Small and Medium Enterprises (MSMEs) in Maluku Province play an important role in driving the local economy. This study discusses the strategic model of MSME development with a focus on financial literacy, digital marketing, and improving the ability of Human Resources (HR). This type of research is quantitative research. The sample of this study was 100 MSME actors in Maluku Province with questionnaire collection techniques. Data analysis tactics using regression analysis with the help of SPSS applications. 20. The result of this study is a strategic model of MSME development with a focus on financial literacy, digital marketing, and improving the ability of Human Resources (HR) can affect the performance of MSMEs both partially and simultaneously. Cooperation between governments, educational institutions, and local businesses is key in implementing in-depth training programs. By strengthening financial literacy, digital marketing, and human resource capabilities, MSMEs in Maluku Province can strengthen the local economy, create jobs, and support sustainable economic growth.